Systematic literature review of qualitative research on stress resilience among breast cancer survivors - Dong, Ruishu; Nur Saadah Mohamad Aun,; Aizan Sofia Amin,; Nazirah Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Breast cancer is the most frequently diagnosed cancer among women, accounting for a quarter of all cancer cases in women. Many studies have demonstrated that increasing resilience benefits cancer control and adaptation. However, current theories of resilience among breast cancer survivors are lacking in terms of comprehensive insights into resilience. Qualitative research data is more helpful in exploring the rich connotation of resilience. Hence, this research is a systematic review of findings from 13 previous qualitative studies on resilience among breast cancer survivors. The findings are categorized into four key themes: (1) the initial stage of resilience is fraught with risks, which include body image distress, illness misperceptions, and emotional distress; (2) resilience emerges through the interaction between the environment and the individual. The impact of individuals is mainly reflected in personal resilience traits, while the environment level is mainly reflected in the family, social, cultural and religious influences; (3) the main coping styles employed by breast cancer survivors include problem-focused coping, emotion-focused coping, and pointless response; (4) the outcomes of resilience include self-awareness and meaning-making, empowerment, transcend oneself and help others. The study concludes that resilience involves a continuous interplay between protective and risk factors, influenced by both individual attributes and environmental conditions. Each encounter with stress or adversity reshapes resilience, leading to a new and dynamic equilibrium. Medical professionals and social workers should address the social and psychological challenges faced by survivors, offering tailored support to foster resilience development.